2021
DOI: 10.1177/0271678x211007960
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular coupling dysfunction in end-stage renal disease patients related to cognitive impairment

Abstract: We aimed to investigate the neurovascular coupling (NVC) dysfunction in end-stage renal disease (ESRD) patients related with cognitive impairment. Twenty-five ESRD patients and 22 healthy controls were enrolled. To assess the NVC dysfunctional pattern, resting-state functional MRI and arterial spin labeling were explored to estimate the coupling of spontaneous neuronal activity and cerebral blood perfusion based on amplitude of low-frequency fluctuation (ALFF)-cerebral blood flow (CBF), fractional ALFF (fALFF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…The ratio of blood supply to neuronal activity could comprehensively depict the NVU modulations in voxel-wise manner and has been introduced as a quantitative imaging marker for cognitive dysfunction assessment. 35,46,47 In accordance with previous investigations utilizing BOLD 48,49 or ASL, 50 the present study obtained significantly altered ReHo and CBF in the vulnerable regions that involved in the management of movement coordination (putamen), control of motor initiation and execution (SMA), and modulation of sensorimotor integration (PG) for PD patients at voxel level. Given that regional hyper-metabolism corresponds to synaptic activation regardless of its excitatory or inhibitory properties, 51 this inverse trend of NVU indicated that the decreased neuronal synchronization (lower ReHo) in motor-related regions is ascribed to the inhibitory effect that is activated via high metabolic supply (high z-CBF).…”
Section: Discussionsupporting
confidence: 90%
“…The ratio of blood supply to neuronal activity could comprehensively depict the NVU modulations in voxel-wise manner and has been introduced as a quantitative imaging marker for cognitive dysfunction assessment. 35,46,47 In accordance with previous investigations utilizing BOLD 48,49 or ASL, 50 the present study obtained significantly altered ReHo and CBF in the vulnerable regions that involved in the management of movement coordination (putamen), control of motor initiation and execution (SMA), and modulation of sensorimotor integration (PG) for PD patients at voxel level. Given that regional hyper-metabolism corresponds to synaptic activation regardless of its excitatory or inhibitory properties, 51 this inverse trend of NVU indicated that the decreased neuronal synchronization (lower ReHo) in motor-related regions is ascribed to the inhibitory effect that is activated via high metabolic supply (high z-CBF).…”
Section: Discussionsupporting
confidence: 90%
“…Traditional and Improved K-Means Algorithm and Mean Shift Algorithm. The mean shift algorithm [24] was introduced and compared with the improved and traditional kmeans algorithms in the term of segmentation error rate, and the results are illustrated in Figure 5. It was found that among the three algorithms, the segmentation error rate was the lowest for the improved k-means algorithm proposed in this research, which was 16.3%; the highest segmentation error rate was found in the traditional k-means algorithm (25.33%); and that of the mean shift algorithm was centered at 19.2%.…”
Section: Comparison On Segmentation Error Rate Among Thementioning
confidence: 99%
“…Functional imaging techniques, such as resting-state functional magnetic resonance imaging (rs-fMRI) and arterial spin labeling ( Zheng et al, 2016 ), have been utilized to detect brain functional alterations in ESRD. Recently, Li et al (2021) investigated disrupted neurovascular coupling in ESRD patients undergoing hemodialysis and revealed it to be a potential neural mechanism for CI. Moreover, rs-fMRI can detect low-frequency (0.01–0.08 Hz) fluctuations in blood-oxygen-level-dependent (BOLD) signals and can be used to investigate spontaneous neural activity at rest ( Barkhof et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%